Synthesis and characterization of a new fluorene ligand and its complexes with cobalt(II), copper(II), and ruthenium(II) - Erden, Ibrahim; Erdogmus, Ali; Demirhan, Nebahat; Avciata, Ulvi (SPRINGER, 2008)
A new fluorene ligand, benzo[15-crown-5]-5H-pyrido[3',2':4,5]cylopenta[1,2-b]pyridin-5-ylidenehydrazone (bph), has been synthesized from the reaction of 4,5-diazafluoren-9-one with 4'-formylbenzo-15-crown-5. The Co(II), Cu(II), and Ru(II) complexes of the ligand were prepared and characterized. The metal-to-ligand ratio of the Co(II) and Cu(II) complexes was found to be 2:1 and that of the Ru(II) complex was found to be 1:1. The ligand and complexes have been characterized by FTIR, UV-visible, H-1 NMR and fluorescence spectra, as well as elemental analyses and mass spectra.
Keywords: Chemistry